Negative associations between maternal prenatal hair cortisol and child socioemotional problems - Mustonen, Paula (Elsevier, 2025)
Maternal prenatal distress can participate in the programming of offspring development, in which exposure to altered maternal long-term cortisol levels as measured by hair cortisol concentrations (HCC) may contribute. Yet, studies investigating whether and how maternal prenatal HCC associates with problems in child socioemotional development are scarce. Furthermore, questions remain regarding the timing and potential sex-specificity of fetal exposure to altered cortisol levels and whether there are interactions with maternal prenatal distress, such as depressive symptoms. The subjects were drawn from those FinnBrain Birth Cohort families that had maternal reports of child socioemotional problems (the Brief Infant-Toddler Social and Emotional Assessment [BITSEA] at 2 years and/or the Strengths and Difficulties Questionnaire [SDQ] at 5 years) as follows: HCC1 population: maternal mid-pregnancy HCC measured at gestational week 24 with 5 cm segments to depict cortisol levels from the previous five months (n = 321); and HCC2 population: end-of-pregnancy HCC measured 1–3 days after childbirth (5 cm segment; n = 121). Stepwise regression models were utilized in the main analyses and a sensitivity analysis was performed to detect potential biases. Negative associations were observed between maternal HCC2 and child BITSEA Total Problems at 2 years but not with SDQ Total difficulties at 5 years, and neither problem score was associated with HCC1. In descriptive analyses, HCC2 was negatively associated with Internalizing problems at 2 years and SDQ Emotional problems at 5 years. A negative association was observed among 5-year-old girls between maternal HCC1 and SDQ Total Difficulties and the subscales of Conduct and Hyperactivity/inattentive problems. When interactions were also considered, inverse associations between HCC2 and BITSEA Internalizing and Dysregulation Problems were observed in subjects with elevated prenatal depressive symptoms. It was somewhat surprising that only negative associations were observed between maternal HCC and child socioemotional problems. However, there are previous observations of elevated end-of-pregnancy cortisol levels associating with better developmental outcomes. The magnitudes of the observed associations were, as expected, mainly modest. Future studies with a focus on the individual changes of maternal cortisol levels throughout pregnancy as well as studies assessing both maternal and child HPA axis functioning together with child socioemotional development are indicated.